171 Nano-structural and Molecular Remodelling Extends to the Remote Region in the Post Myocardial Infarcted Porcine Heart â€" A Basis for Heart Failure Development?. (3rd June 2016) - Kitmitto, Ashraf; Nossier, Mahmoud M; Bennett, Hayley J; Pinali, Christian; Davenport, Bernard; Walker, Rachel; Murfitt, Lucy; Malik, Nadim; Holt, Cathy
Abstract : Introduction: A common consequence of coronary artery disease is myocardial infarction (MI). Following an MI a sequence of pathological events occur with necrosis and acute inflammation leading to the formation of a stable fibrous scar. However, although many patients now survive an MI many also go on to develop heart failure (HF), with cellular remodelling implicated as a precipitating factor. However, the nano-architectural changes and associated molecular remodelling remains poorly understood. Mitochondria occupying between 30–40% of the cardiomyocyte volume, play a central role in cardiac energetics, with evidence to indicate dysfunction in the post-MI heart. 1 Here we have combined 3-D electron microscopy with biochemical and quantitative mass spectrometry methods, to investigate morphological changes to mitochondria within both the peri-infarct and remote regions. We have interrogated structural changes in the context of protein, molecular, level remodelling. Methods and results: We have employed a translationally relevant porcine model of MI, presenting mild to moderate left ventricular dysfunction (n = 3, control and MI). 2 Animals were studied 1 month post-MI when the scar region has stabilised. Tissue was sampled from the peri-infarct and remote regions and a corresponding region from the control hearts, fixed and prepared for serial block face scanning electron microscopy as previously described. 3 Tissue was also lysed and analysed by quantitative mass spectrometry and western blotting. 3-D reconstruction of the mitochondria within both the peri-infarct region and remote area determined that they were smaller in terms of volume (no. of mitochondria = 389, P < 0.01; no. of mitochondria =262 P < 0.05 respectively) compared to control. There was also a change to the distribution of the subsarcolemmal and inter-fibrillar mitochondria in both regions post-MI. Quantitative mass spectrometry identified between 1400–2000 proteins within each tissue sample with alterations (both up and down regulation) of proteins associated with Î² oxidation and OXPHOS. Conclusion: These data reveal that mitochondrial structural rearrangements are accompanied by expression level changes to proteins regulating cardiac energetics. Importantly, the data also indicate that while morphological remodelling is more acute within the peri-infarct region the remote areas of the infarcted heart are also undergoing cellular maladaptations. Currently, there are no treatments that specifically target cellular structural remodelling post-MI. Here we show that mitochondrial remodelling is a feature of the post-MI heart; targeting these changes at the structural and molecular level may represent a novel treatment strategy for improved outcomes. References: Dodd, M. S., Atherton, H. J., Carr, C. A., Stukey, D. J., West, J. A., Griffin, G. K., Radda, K., Clarke, K., Heather, L. C., Tyler, D. J. Impaired in-vivo mitochondrial Krebs cycle activity after myocardial infarction assessed using hyperpolarized magnetic resonance spectroscopy. Circ Cardiovasc Imaging . 2014;7(6);895-–904 Malik N, Farrell KA, Withers SB, Wright EJ, Holt CM. A novel porcine model of early left ventricular dysfunction for translational resaerch. Research Reports in Clinical Cardiology. 2013;4:1–7 Pinali C, Bennett H, Davenport JB, Trafford AW, Kitmitto A. Three-dimensional reconstruction of cardiac sarcoplasmic reticulum reveals a continuous network linking transverse-tubules: this organisation is perturbed in heart failure. Circ Res. 2013;113:1219–30